Application of Bio-inspired Optimization Techniques in Agriculture and Food Processing - Panigrahi, Rajashree; Patra, M.R.; Sankhla, Sneh (Annals of Agricultural Research, 2016)
Agriculture is expected not only to feed the world but also to satisfy the nutritional requirements.With the advent of global free trade regime; pursuit for enhancing the production and productivity; conserving natural resources; newer biotic and abiotic challenges; and adaptation to the global climatic changes agriculture has become more complex. The complexity has to be adequately defined and controlled in order to achieve the goals of sustainability and profitability of agriculture. Bioinspired optimization techniques are a class of biologically-inspired systems which look for solutions by adapting to the basics of various biological activities occurring around us. This paper provides an overview of nature inspired techniques like artificial intelligence, expert system, computational intelligence, swarm intelligence etc. which have been effectively and efficiently used for solving complex problems and for agricultural and food applications like diagnosis of diseases, data mining, image processing, forecasting problems, etc.